REFLEKSI SPIRITUAL MENGGAPAI PUNCAK TAKWA (KAJIAN TAFSIR TEMATIK MENJALIN KOMUNIKASI BERSAMA ALLAH SWT) - Otong Surasman (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
At a time when the condition of Muslims in facing the challenges of the times, after receiving national and even global examinations with the outbreak of covid-19, made some human beings, especially Muslims, experience complacency in carrying out worship in congregation, because there is a prohibition on keeping a distance in order to avoid the transmission of COVID-19. -19. So the most important move to revive worship and muamalah, it is very important to re-understand his identity as a pious person. Spiritual reflection reaching the pinnacle of piety is a powerful concept. so that Muslims take the time to communicate with Allah SWT through the concept of